Incidence and risk factors of anaemia among people on antiretroviral therapy in Harare - Linda A. Mandikiyana Chirimuta; Tinei Shamu; Cleophas Chimbetete; Chérie Part (AOSIS, 2024)
Background: Anaemia is associated with reduced quality of life and increased mortality risk among people living with HIV (PLHIV). Although antiretroviral therapy (ART) reduces the prevalence of anaemia, some patients remain at risk after commencing ART. Objectives: We estimated the incidence of anaemia after ART commencement and identified associated risk factors. Method: We analysed outpatient records at Newlands Clinic, Harare, Zimbabwe. Patients (≥ 5 years old) who were commenced on ART between January 2016 and December 2020 were included and were followed up for up to 2 years. Patients with anaemia at ART commencement and women who were pregnant at any time during follow-up were excluded. Cox proportional hazards regression was used to assess independent risk factors for anaemia. Results: During the study, 1110 patients ≥ 5 years old were commenced on ART with a prevalence of anaemia of 40.0%. Five hundred and twenty-nine patients met the inclusion criteria and were followed up for 823.7 person-years. The median age was 36.1 years and 290 (58.4%) were female. The incidence rate of anaemia after ART commencement was 176.1 per 1000 person-years (95% confidence interval [CI]: 149.6-207.2). Females (aHR: 2.09; 95% CI: 1.46-3.00, P  0.001), zidovudine use (aHR: 3.50 96% CI: 2.14-5.71, P  0.001), age 5-12 years or 50 years, and the presence of World Health Organization stage III/IV disease (aHR: 2.19; 95% CI: 1.14-5.71, P = 0.019) had higher odds of developing anaemia. Conclusion: The incidence of anaemia after ART commencement was high. Female sex, zidovudine use, age and the presence of stage III/IV disease were independent risk factors for anaemia. Clinicians should screen PLHIV on ART regularly for anaemia.  What this study adds: This study found a high incidence of anaemia among PLHIV after commencing ART and identified several risk factors.